Quantitative light-induced fluorescence method in comparative assessment of enamel remineralization indicatiors in vivo and during remineralizing therapy - Гегамян, А.О.; Лыткина, А.А.; Сарап, Л.Р.; Зейберт, А.Ю. (Actual Dentistry, 2021)
Abstract. This article evaluates the rate of remineralization of enamel in patients with focal demineralization after treatment with fixed orthodontic appliances (braces) with Qraypen™ intraoral camera and Qray software (Inspektor Research Systems BV) in two comparative groups. In the first group, natural remineralization through restorative properties of saliva was considered, in the second group, gel R.O.C.S. Medical Minerals was used for enamel remineralization. In the course of evaluating the results of remineralization, obtained in the comparative groups, it was concluded that the complete restoration of enamel due exclusively to the remineralizing properties of saliva in patients after orthodontic treatment did not take place. Conversely, in the group, where R.O.C.S. Medical Minerals gel was used to remineralize enamel, the level indicator of mineral components loss decreased by 20 % after two weeks of its use, and by the sixth week it reached indicators of a decrease in the demineralization level of 50 % from initial one. Key words: remineralization, saliva, quantitative light-induced fluorescence, R.O.C.S. Medical Minerals.